Multi-stage point estimation of the mean of an inverse Gaussian distribution. Issue 1 (2nd January 2019) - Chaturvedi, Ajit; Bapat, Sudeep R.; Joshi, Neeraj
Abstract: In this article, we develop two-stage, three-stage, and accelerated sequential procedures for the point estimation of the mean μ of an inverse Gaussian distribution when the scale parameter λ is unknown. Both minimum risk and bounded risk estimation problems are considered subject to a weighted squared error loss function. We aim at controlling the associated risk functions for all three procedures. Second-order approximations are obtained for the proposed procedures.